If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 = 4 + x Solving -5 = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + -1x = 4 + x + -1x Combine like terms: x + -1x = 0 -5 + -1x = 4 + 0 -5 + -1x = 4 Add '5' to each side of the equation. -5 + 5 + -1x = 4 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 4 + 5 -1x = 4 + 5 Combine like terms: 4 + 5 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9
| -15-4x=45 | | 2n+109=12n-1 | | -24-9x=-78 | | 2*8/2+6/3-12*2 | | 5k+122=16k+12 | | -10-84=-234 | | y=-7*0+1 | | 6x+20=14-68 | | 4*5/2 | | -2x-13=4x+17 | | .50x+0.25(30)=33.5 | | 6x-1=4x+15 | | 11x^2-24x-4=0 | | x+2/2=7 | | 12/4*5 | | 3x-7y=8 | | 9x-12=6+3 | | 8a-3(2a-5)+6= | | 2x-3=13-2x | | (x+1)^1/2=5-x | | -2(4x-1)=8 | | 2x-152=232-10x | | -10x-84=-234 | | 3*(-12)/(-4)+2*(-12-7) | | h=40t+200 | | (3/4)*(x-1) | | -3x+3=-3(2x+3) | | 5g+74=12g+11 | | 7x+3=-7+4x+16 | | 5=3-2 | | -7(-2x+5)=-203 | | -3/110+2 |